Planning Change in an Organization; MCB Bank Limited, Pakistan - Fazal Haleem (Journal of Central Banking Theory and Practice, 2015)
This paper is primarily based on a case study of a leading bank in Pakistan, that is, MCB Bank Ltd. Four established change models have been applied to the bank to find out how a change comes in/ is brought in, managed, and how it affects organizational environment and its stakeholders, particularly customers and employees. The four established change models applied are the change management approach by Ansoff and McDonnell; the change management model by Kurt Lewin; the 7S framework by Thoman J. Peters and Robert H. Waterman; and the change management model developed by Stephanie Elam. The study covers a change management aspect such as strategic intervention technique; a need for change management; resource implication; planning change; strategies in change management; system effectiveness; managing resistance to change; leadership issues; cultural issues; people issues; external environment issues; workable approach to overcome change resistance; appropriate model and implementing the model.
Keywords: O33; 330; Banks and Change Management; Technology and Banks; Innovation and Banks